Efficacy of silymarinum at chronic diffuse liver diseases - A. V. Matvieiev; E. I. Konyaeva; N. V. Matvieieva (Российский журнал гастроэнтерологии, гепатологии, колопроктологии)
The aim of review. To present modern data of foreign literature on efficacy of preparation of Silybum marianum – silymarinum at patients with alcoholinduced liver disease, non-alcoholic steatohepatosis and primary biliary cirrhosis.Original positions. Analysis of literary data demonstrated, that silymarinum is a safe pharmaceutical and, despite of a plenty of clinical and experimental publications, its efficacy at alcoholic liver disease and primary biliary cirrhosis requires further studying as series of systematic reviews and metaanalyses are subject for discussion due to the absence of uniform methodological approaches, application of drugs with different pharmakokinetics and because of ignoring of evidencebased medicine requirements.Conclusion. Application of the uniform silymarinum standard and carrying out of further investigations adhering to requirements of evidence-based medicine, should finally resolve present contradictions in assessment of efficacy of standardized silymarinum in patients with alcoholic liver disease, non-alcoholic steatohepatosis and primary biliary cirrhosis.